In silico Evaluation of Quercetin and Apigenin from Litsea angulata as Potential Dual Binders of DPP-4 and SUR1 - Aulia Rhamadani Arfan; Nabila Hadiah Akbar; Taufik Muhammad Fakih; Tegar Asandra Ghifari; Sulthan Waliid Anggara Wisesa (Journal of Pharmascience, 2026)
Litsea angulata leaves have traditionally been used for diabetes management; however, the molecular mechanisms underlying their antidiabetic activity remain poorly understood. This study aimed to evaluate the interaction potential of two major flavonoids from L. angulata, quercetin and apigenin, against two protein targets associated with type 2 diabetes mellitus: dipeptidyl peptidase-4 (DPP-4, PDB ID: 1X70) and sulfonylurea receptor 1 (SUR1, PDB ID: 5YKG). Ligand structures were optimized using density functional theory at the B3LYP/6-31G level, followed by molecular docking simulations using AutoDock Vina. Sitagliptin and glibenclamide were used as reference ligands for DPP-4 and SUR1, respectively. The docking results showed that quercetin and apigenin exhibited moderate binding affinities toward DPP-4 (–8.0 and –7.5 kcal/mol), interacting with key residues including Arg125 and Tyr547. In contrast, both flavonoids demonstrated stronger predicted binding energies toward SUR1 (–9.1 and –9.0 kcal/mol) compared with glibenclamide (–8.8 kcal/mol), although the interactions occurred at residues different from the primary functional binding site. The protein–ligand interactions were mainly stabilized by π–π stacking and van der Waals interactions rather than strong hydrogen bonds. Additional in silico analysis indicated that both compounds possess favorable physicochemical and pharmacokinetic properties based on ADME prediction, while toxicity assessment suggested relatively acceptable safety profiles. These findings indicate that quercetin and apigenin may serve as promising flavonoid scaffolds for the development of antidiabetic agents targeting multiple proteins involved in glucose regulation. Further experimental studies are required to validate their pharmacological activity and clarify their mechanisms of action.